Far away and long ago. Carmen de Patagones in the first half of 19th Century (Quinto Sol, 2013)
In 1779 the fort of Carmen de Patagones was founded in the South of the current province of Buenos Aires in response to the Borbons politics to ensure the territorial control of its colonial dominions. The purpose of the paper is to analyze the development of this town from its establishment to the Rosas government period, recognizing different stages. The first one makes reference to the process of occupation of the land through a particular relation with the native groups of the zone. In a second stage, the fort obtains a relative autonomy in the handling of its political and administrative matters. And in the third one, the government attempted –with relative success-  to limit this autonomy exerting a greater control on the life of the fort.
Keywords: Frontier; interethnic relations; Rosas government